Numerical simulation and experimental study of the electroosmotic flow in open microfluidic chip based on super-wettability surface - Jiang, Shuyue; Zhang, Haifeng; Chen, Liang; Li, Yiping; Sang, Shengtian; Liu, Xiaowei (Colloid and interface science communications, 2021)
The traditional bonding technology severely limits the development of microfluidic chip owing to the complicated techniques, the blockage and deformation of microchannels, etc. In this paper, an open microfluidic chip based on super-wettability surface is proposed to avoid the bonding technology. The feasibility of open microfluidic chip based on capillary electrophoresis is demonstrated from the analysis of electroosmotic flow. In theory, we build simulation model to study the flow field of the open microchannel. The electroosmotic flow (EOF) velocity of an open microchannel (0.477 mm/s) is bascially euqal to a closed microchannel (0.479 mm/s). In experiment, the open microfluidic chip based on super-wettability surface is fabricated by chemical etching and laser ablation. The EOF velocity and electroosmotic mobility of open microfluidic chip are 1.05 mm/s and 4.2 × 10−4 cm2/(V·s), respectively. As a result, this open microfluidic chip can obtain the stable electroosmotic flow. Finally, under the action of electroosmotic flow, potassium ferricyanide is transported from the reservoir to the detection area by measuring the cyclic voltammetry curve.We envisage that this will also open up research avenues on open microfluidic chip, an area that still exists undeveloped. [Display omitted] •A novel open microfluidic chip based on a super-wettability surface is proposed.•The microfluidic chip with super-wettability surface can obtain stable electroosmotic flow.•The microfluidic chip with super-wettability surface is fabricated by chemical etching and laser ablation.